2008
DOI: 10.1016/j.ijid.2007.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory features of Crimean-Congo hemorrhagic fever: predictors of fatality

Abstract: Thrombocytopenia of < or = 20 x 10(9)/l, a prolonged aPTT > or = 60s, the existence of melena, and somnolence were independent predictors of fatality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
148
3
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(180 citation statements)
references
References 20 publications
22
148
3
7
Order By: Relevance
“…Experience over the past decade in Turkey has shown that gingival bleeding, ecchymoses, hematemesis, diarrhea, melena, confusion and somnolence are significantly more common in fatal cases (Ergonul et al, 2006a;Cevik et al, 2008;Hatipoglu et al, 2010). Lethal illness was associated with more severe thrombocytopenia, more prolonged PT and aPTT, lower fibrinogen levels and increased serum AST and ALT (Ergonul et al, 2006a;Ozkurt et al, 2006;Onguru et al, 2010).…”
Section: Predictors Of Survival or Deathmentioning
confidence: 99%
“…Experience over the past decade in Turkey has shown that gingival bleeding, ecchymoses, hematemesis, diarrhea, melena, confusion and somnolence are significantly more common in fatal cases (Ergonul et al, 2006a;Cevik et al, 2008;Hatipoglu et al, 2010). Lethal illness was associated with more severe thrombocytopenia, more prolonged PT and aPTT, lower fibrinogen levels and increased serum AST and ALT (Ergonul et al, 2006a;Ozkurt et al, 2006;Onguru et al, 2010).…”
Section: Predictors Of Survival or Deathmentioning
confidence: 99%
“…The overall mortality rate of CCHF disease was 17.3% in this study. Our mortality rate is higher than the average for Turkey (5.4%) (32). In the current study, decreased platelet counts, increased LDH and prolonged aPTT were identified as predictors of mortality in univariate analysis.…”
Section: Discussionmentioning
confidence: 38%
“…Serum ChT could be a prognostic marker in patients with CCHF. Different predictors of fatality were reported as risk factors for CCHF (27,(29)(30)(31)(32), and those previously defined severity criteria were not always consistent. These criteria include decreased platelet counts, prolonged aPTT, increased AST, ALT and LDH activities in a univariate analysis from five different studies.…”
Section: Discussionmentioning
confidence: 82%
“…6 In trials conducted on CCHF, leukocytosis, elevated ALT and AST, PT and aPTT and LDH (lactate dehydrogenase) values were used in assessing prognosis. 4,11,12 No information is available in the literature indicating the role of blood groups in the prognosis of CCHF. In the current trial, high ALT and AST levels and low leukocyte and platelet values were observed, in accordance with the results of other trials.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The disease is prevalent in a wide geographic area encompassing Asia, Eastern Europe, Africa, and Russia. 3,4 Since 2002 it has been seen in central, northern, and eastern regions of Turkey. 5 CCHF is transmitted to humans via tick bites and may lead to symptoms of fever, nausea, asthenia, headache, abdominal pain, diarrhea, myalgia, petechia, and bleeding.…”
Section: Introductionmentioning
confidence: 99%